Speak-Co English Training for Prospective MSME in Selosari Village, Magetan - Tri Wahyuni Chasanatun; Sri Lestari (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The training for Family Welfare Program (PKK) as potential Micro, Small Medium Enterprise (MSME) actors in Magetan is to equip women with English language competence, especially in transactional and introduction to vocabulary related to buying and selling food. Therefore, they can promote, buy, and sell products in English after participating. English language training, called Speaking-Conversation (Speak-Co) for MSMEs in Selosari Village, Magetan was carried out in August-September 2021. The training was related to introducing vocabulary, describing and promoting products, and practicing conversation about buying and selling products produced by MSMEs. The training began with providing information on language related to food, buying and selling, and s of English text about food descriptions. Then proceed with giving examples of reading English texts with the correct speech by the rules of English speech. The participants listened and imitated how to read the text correctly, practicing reading text by text. One by one, the training participants made presentations in English on describing and promoting their individual and buying and selling dialogues. During the training, participants were given examples, comments, suggestions, corrections of speech, grammar, intonation, and how to convey the material’s content. After this training, MSME actors could master the related vocabulary and be confident in presenting their products, but the limitation was that 50% of them had difficulty communicating directly.